Pengaruh Good Corpotare Governance terhadap Kepatuhan Perusahaan dalam Menunaikan Zakat Perusahaan dengan Profitabilitas sebagai Variabel Moderasi : Studi pada Seluruh Bank Syariah - Kiran Nisa; Anggita Ayudya Pratiwi; Hasnawati A. Lagaligo; Winda Winda; Bintang Bintang; Raisa Hania; Inaya Hairul Nisa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG) on corporate compliance in paying corporate zakat with profitability as a moderating variable. The study uses a quantitative approach with secondary data in the form of financial reports of Islamic Commercial Banks in Indonesia for the period 2019–2024. The sampling technique uses purposive sampling to obtain 6 Islamic Commercial Banks with a total of 36 research observations. The independent variable in this study is Good Corporate Governance (GCG), the dependent variable is the fulfillment of corporate zakat payments, while profitability is positioned as a moderating variable. Data analysis was carried out using Moderated Regression Analysis (MRA) with the help of the SPSS application. The results show that Good Corporate Governance has a significant effect on corporate compliance in paying zakat in a negative direction. Profitability has a significant positive effect on the existence of corporate zakat. In addition, profitability is able to strengthen the relationship between Good Corporate Governance and corporate compliance in paying zakat. The coefficient of determination value shows that the research model is able to explain the variation in corporate zakat fulfillment by 42.9%, while the rest is influenced by other factors outside the research model.